COMPARATIVE STUDY BETWEEN REMOVERS AGENTS OF SILICON INTO THE SYNTHESIS OF MICRO/NANO-STRUCTURED PYROLYTIC CARBON FROM REFINED SUGAR - David Macias-Ferrer, José A. Melo-Banda, Rebeca Silva-Rodrigo, Mayda Lam-Maldonado, Ulises Páramo-García, Marco A. Meraz-Melo (International Journal of Research Science and Management, 2018)
The present study deals with a comparison between HF and NaOH with different concentration, as removers agents of silicon into the synthesis of micro/nano-structured pyrolytic carbon (MNC) via nanocasting method, using SBA-15 as hard template. SBA-15 was prepared through sol-gel using pluronic P-123 as surfactant and tetraethoxysilane as a silicon precursor. MNC was synthesized by the nanocasting method and anhydrous pyrolysis at 800 °C using SBA-15 as structure directing agent and refined sugar as a carbon precursor. Testing six samples of MNC, the silicon removal was carried out employ solutions 1M NaOH, 2M NaOH, 4M NaOH, 8M NaOH, 8.6M HF and 28.9M HF by 24 h. The prepared materials were characterized by means of N2 physisorption analysis, SEM, EDS, FTIR and Raman spectroscopy. EDS analysis revealed that 8.6M HF and 8M NaOH had the highest removal efficiency of silicon, detecting 0.21% wt Si and 0.32% wt Si respectively versus 23.8% wt Si before this process, however, using solutions of a low concentration of NaOH, a silicon weight percentage lower than 0.6% is detected. Therefore, the HF could be replaced by NaOH avoiding possible damage to the structure of MNC due to the effect of HF and contributing to the safety of researchers and the environment.